Effect of Intracellular Trehalose on Post-Thaw Survival of Saccharomyces cerevisiae Yeast Cells - Ponomareva, Viktoria L.; Vysekantsev, Igor P.; Onasenko, Elena S. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(3):268-272.